EFFECT OF ADDITION OF YEAST AND OLD TIME FERMENTATION TO VOLUME DONAT - Mulyatiningsih, Endang (Jurnal Penelitian Saintek, 2015)
This research is aimed at: 1) finding out the influence of increasing the amountof yeast and fermentation time to the volume oj doughnuts, 2) finding out the minimum amount of yeast effective in doughnut formula, and 3) finding out thelength of fermentation time ideal for each doughnut formula with different percentage of yeast. The research uses experimental approach took place in the laboratory of Food Science, Department of Family Welfare Education, Faculty of Technology, Yogyakarta State University. Variables involved in this research consist of independent variables, i.e. different amount of yeast 1.1 %, 1.63%, and2.2%; length of fermentation time 45’, 60’, 75’, 90’, 105’, and 120’; and dependent variable of the volume of doughnuts, controlling variable of thevolume of doughnuts beforefermentation. The mixing of ingredients to make the dough uses the straight dough method The research is controlled by means of carefully scaling the ingredient using sartorial scale with the level of accuracy up to one milligram, standardizing the temperature while fermentation and measuring the volume using the landscape method and. the data are analyzed further by means of two-way Anava. When any difference is obtained, the advanced- test Anava is performed using Duncan’s Multiple Range Test(DMRT). The result of the research shows that: 1) there is significant difference of the doughnut volume based on various amount of yeast and length of fermentation time; 2) 1.1% of yeast is still effective to enlarge the volume of doughnuts without any significant difference based on the analysis of DMRT on the three different formulations with 90-minutefermentation time, and thus the ideal fermentation time for the three formulation tested is 90 minutes because over 90 minutes the dough will have got over proofing.